2021
DOI: 10.1038/s41598-021-86767-1
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane-functionalized starch nanocrystals as anti-tuberculosis drug carrier

Abstract: Studies related to loading ability and delivery of clinically used first-line anti-tuberculosis drugs (ATDs) such as isoniazid, rifampicin, pyrazinamide and streptomycin on the surface of starch-derived bulk and nanopolyurethanes (SBPUs and SNPUs) as drug delivery systems (DDS) have been focused to minimise or remove the drug-associated adverse effects. The efficiencies of nanopolyurethanes obtained from the differently substituted cyclic aliphatic and aromatic isocyanates have been studied for drug loading an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Commercially available drugs are pyrazinamide (PZA), isoniazid (INH), streptomycin (SM) and rifampicin (RIF). However, due to genetical, molecular and structural changes, these drugs cause either increased relapse of TB with noncompliance or severe multi/extreme drug-resistant (MDR/XDR) tuberculosis. ,, …”
Section: Specific Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Commercially available drugs are pyrazinamide (PZA), isoniazid (INH), streptomycin (SM) and rifampicin (RIF). However, due to genetical, molecular and structural changes, these drugs cause either increased relapse of TB with noncompliance or severe multi/extreme drug-resistant (MDR/XDR) tuberculosis. ,, …”
Section: Specific Diseasesmentioning
confidence: 99%
“…Rather than developing new drugs or including new drug carriers, efforts focus on enhancing bioavailability, distribution, metabolism, and stability, therapy shortening, target modification, improving drug availability, and reduction of resistance to existing drugs. To meet the challenges a number of polymer therapeutics were developed including chitosan, polylactic- co -glycolic acid (PLGA), polyurethane (PU), metal (gold) nanoparticles (NPs), super paramagnetic iron oxide NPs, , inorganic molecules (silica (SiO 2 ), and CdS and carbon quantum dots (CQDs)) which are used as drug/vaccine carriers. Recent approaches for the same using polymers are discussed in the following section.…”
Section: Specific Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanotechnology can be applied to the delivery of drugs, providing a new way of cancer treatment. In the past decade, it has been found that materials that can be used as drug carriers include polyurethane functionalized starch ( Desai et al, 2021 ), ferritin( He et al, 2019 ), gold nanoparticles (AuNPs) ( Li et al, 2019 ), cyclodextrin ( Kang et al, 2019 ), and silk fibroin ( Kapoor and Kundu, 2016 ; Melke et al, 2016 ). Among them, silk fibroin, a typical natural biomaterial, exhibits versatile properties through tuning the secondary conformations and hierarchical microstructures ( Ma et al, 2020 ).…”
Section: Drug Delivery System For Chemotherapy Of Silk Fibroinmentioning
confidence: 99%